Managing foreign exchange risk of a small Brazilian importer - Hsieh, Paola Rouhlin (2021)
Currency risk is a recurring theme in companies today. Even for those who do not trade foreign currencies directly, there is still a conversion exposure that cannot be ignored in risk management. The present study proposes to develop an exchange rate management policy for a small Brazilian importer. A case study of the company PPbr (pseudonym) was elaborated, who supplied data from recent years to build a FX risk management policy. To do so, I proposed a hedging strategy using NDF with maturation in 30, 60 and 90 days; based on two types of analysis: two-way sensitivity analysis and Monte Carlo simulation, obtaining the optimal hedge range for the company. To verify the solution's efficiency, I prepared a back test, using data from 2021 and compared the results using two methodologies: (1) a t-test for the liabilities quoted in USD; and (2) a Sharpe ratio comparison between the unhedged solution and the proposed solution. The comparison demonstrates no predilection between the solutions. The Sharpe ratio of the unhedged strategy is extremely close to the hedged one, showing that the risk - return of the hedged strategy may not compensate to adopt hedged position; whereas the return of the t-test demonstrates there is no statistical significance difference between the strategies.